Clinico-Therapeutic Study Of Ruminal Lactic Acidosis In Goats - Anil J Thachil (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2000)
Twelve goats with history and symptoms suggestive of ruminal acidosis were divided into two groups (I and 11). Six healthy goats were also served as controls. Detailed clinical examination, recording of clinical data, sampling and analysis of rumen liquor and blood were done at zero hour, one hour, 12 h, 24 h, 48 hand 72 h of the study. Therapeutic management of group I was done by giving five per cent sodium bicarbonate solution intravenously at a dose rate of 5 ml / kg ; whereas in group 11 it was replaced with a mixture of sodium carbonate and sodium bicarbonate (carbicarb) intravenously at a dose rate of 4 ml / kg. Animals of group I and 11 were given dexamethasone 20 mg intravenously, evacuated rumen contents and given ..